Two decades of research on autoimmune liver disease in Turkey - Demir, Nurhan; Ekin, Nazım; Torgutalp, Murat; Wahlin, Staffan; Efe, Cumali (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Autoimmune hepatitis (AIH), primary biliary cholangitis (PBC), and primary sclerosing cholangitis (PSC) are the 3 main autoimmune liver diseases (AILDs). The epidemiology of AILD in Turkey is not known. To determine the scientific status, we performed a scientometric analysis of AILD-related original articles that originated from Turkey. Materials and Methods: We searched the Web of Science database, the Science Citation Index Expanded (SCI-E), and the Social Sciences Citation Index (SSCI) by using the keywords “autoimmune hepatitis,” “primary biliary cholangitis/primary biliary cirrhosis,” and “primary sclerosing cholangitis” in conjunction with “Turkey.” A scientometric analysis was done on the search results. Results: We identified 117 AILD-related papers that were published in Turkey from 1997 to 2019. Among these, 70 case reports, letters, and reviews and 2 original articles that were not cited in SCI-E/SSCI were excluded. The remaining 45 original articles were further analyzed. These studies were related to AIH (n=22), PBC (n=7), PSC (n=9), PBC-AIH overlap (n=5), and others (n=2). Four of the publications originated in pediatric settings; 9 of 45 papers were published from 1997 to 2008 and 36 papers were published from 2009 to 2019. Most papers (75%) were reported from 5 centers; 9 papers (20%) were published in journals with an impact factor of 3 or higher. Conclusion: The overall number and quality of AILD-related papers in Turkey are unexpectedly low, although a number of papers have received considerable international recognition. More epidemiologic, prospective, and multicenter research projects are warranted to advance AILD knowledge and to produce high-quality research from Turkey.